The Contemporary Academic Library Resource Sharing Mission: Fragmentation or Evolution?. Issue 3 (15th May 2017) - O'Brien, Kevin
ABSTRACT: Academic interlibrary loan practitioners are experiencing changes that can be characterized as either the fragmentation of the resource sharing mission or its evolution into a new form of service routinely making use of new and diverse sources of information outside the scope of past practices. Among these new sources are curated repositories of open access literature, institutional repositories, digital libraries containing scanned public domain literature, and social media article-sharing networking sites. The incorporation of these sources of information into regular workflows presents interlibrary loan practitioners with many challenges. This paper will discuss ways to address these developments.